The effect of target size and eccentricity on reflex disparity vergence - Stevenson, Scott B; Reed, Paul E; Yang, Jian (Vision research (Oxford), 1999)
This study examined the effects of stimulus size and eccentricity on reflex disparity vergence: the small, involuntary corrections of eye alignment which serve to minimize the binocular disparity of fixated targets. Subjects were instructed to fixate steadily on a small, stationary mark superimposed on the center of a dynamic random dot stereogram. The stereogram was binocularly uncorrelated except for a fully correlated patch whose size and eccentricity were varied systematically across trials. The disparity of the patch was varied sinusoidally over time to stimulate vergence following movements. The overall purpose was to determine the relative contributions of various field loci in controlling binocular fixation by finding the smallest patch which would reliably drive vergence against the effort to fixate steadily. Psychophysical thresholds for detection of the correlated patch stimuli were also measured for comparison to the oculomotor results. Results showed that the smallest effective patch increased with eccentricity similarly for both vergence responses and psychophysical detection, suggesting they depend on a common, presumably cortical matching process. The dependence of response on eccentricity is roughly consistent with changes in the cortical magnification factor, suggesting that the area of cortex stimulated may be the determining factor in vergence responses to this class of stimulus.